Effects of Sweet Sorghum Harvest Systems on Raw Material Quality - Gravatim Costa, Gustavo Henrique; Ciaramello, Sandro; Giachini, Jorge Wilson; Buzzolin Gazzola, Willian Cesar; Giachini, Lucas Emilio; Martinez Uribe, Raul Andres [UNESP] (Springer, 2018)
The harvest of sweet sorghum has been studied in several countries because it increases the costs. However, it could decrease the quality of raw material destined to ethanol production. Therefore, the goal of this study was to analyse the quality of the raw material coming from two different sorghum cutting typesand at different processing times. At 120days after sowing, the harvest was carried out manually, the sorghum being chopped into 20-cm billets, and a portion of the stalks were shredded in a forage chopper, resulting in particles of 2-3cm in diameter. The broth was extracted through a hydraulic press at 0, 6, 12 and 24h after cutting and characterized. We concluded that the billets was the most suitable for the sorghum, since there was less deterioration of the plant in relation to the cut into forage form and the plant processing must occur within 6h for the best possible use of the material.
Keywords: Sucroenergy; Bioenergy; Billet; Forage; Biofuel; Bioethanol